PROSPECTS OF THE SHANGHAI COOPERATION ORGANIZATION: UZBEKISTAN'S APPROACHES (Scientific journal of the Fergana State University, 2024)
The article reveals the role and place of the Shanghai Cooperation Organization (SCO) in the foreign policy of the Republic of Uzbekistan. Based on the justification of the issue of reforming and improving the activities of the SCO as priority issues on the organization’s agenda, Uzbekistan’s fundamental approaches to this issue are revealed.